Recognition of Sesquiterpenoids and Piperidine Alkamides as Two Discerning Metabolite Classes in the Fruits of Piper nigrum 'Semongok Aman' - Osman, Muhamad Faris; Faudzi, Siti Munirah Mohd; Shaari, Khozirah; Sarbini, Shahrul Razid; Khamis, Shamsul (Universiti Malaysia Sarawak, 2025)
The Malaysian Pepper Board (MPB) has recommended the plantation of three over seven Piper nigrum L. cultivars, owing to their beneficial agronomic traits. Currently, distinction between the cultivars is assessed based on morphological characters. The MPB has also proposed the concept of monovarietal farm, which is believed to have the potential of strengthening the quality of pepper in the global market. However, there remains a need for a fair assessment of the specialised metabolites’ variation among P. nigrum cultivars in search of a cultivar with distinctive metabolites profile, which may be the most suitable candidate for the application of such concept. We hereby describe revised protocols aimed at minimising the oxidation of the fruits of five P. nigrum cultivars and reducing the experimental run time that allowed utilisation of the same samples in GC-MS and1H-NMR metabolomics. Subsequently, feature-based molecular network (FBMN) was used to verify the patterns observed in the principal component analysis (PCA) of the1 H-NMR and GC-MS data. PCA of both datasets revealed that the clustering pattern of the five cultivars paralleled the origin of their parent plants, with the genetically more similar cultivars, 'Kuching', 'Semongok Emas', 'India', and 'Yong Petai', being closer to each other compared to 'Semongok Aman'. 'Semongok Aman' was found to contain a higher abundance of the sesquiterpenoids germacrene B and γ-elemene, as well as the piperidine alkamides piperine and its isomers. FBMN further highlighted the higher abundance of the two metabolite classes in the fruits of 'Semongok Aman'. 'Semongok Aman' might be a suitable cultivar for the implementation of monovarietal pepper farm concept owing to its distinctive metabolite profile.